Six sigma execution: How to World's greatest companies live and breathe six sigma (sách photo) - Eckes George (McGraw-Hill, 2005)
In six Sigma excution, Ecker draws on his vast professional experience to describe the business acumen and leadership skills needed to effectively incorporate Six Sigma into organization's DNA, executing initiatives throughout the entries company. He delivers a practical blueprint that simulates the training and coaching session used with his own clients, providing you with the dialogue, tools, tactics, and cautionary, advice you can use to spearhead and deploy a Six Sigma effort of any size.